PEMBELAJARAN SASTRA PROFETIK SEBAGAI MEDIA PENGEMBANGAN KARAKTER SISWA - Anwar Efendi (Jurnal Cakrawala Pendidikan, 2011)
Abstract: Prophetic Literature learning as a Medium to Develop Student Character. Recently, the character education mainstreaming has been boosted in the national education development. Substantially, the concept of character education is included in the formulation of the national education goals. Therefore, one important aspect in the context of character education is the collective consciousness of all parties involved in the activity. One attempt to develop character is through literature learning, including prophetic literature. Prophetic literature learning can provide joy of life and balance between thoughts and feelings. In such a way, students’ dignity is respected and they become whole human beings who possess knowledge, skills, good heart, and sensitivity.Keywords: education goals, literature learning, character building